Combustion processes of rice husks for energy - Ismail, Ahmad Faris; Yusaf, Talal F.; Mahdi, Faisal M.A.; Shamsuddin, Abdul Halim (Asian Institute of Technology RERIC, 1997)
A very comprehensive study of the Rice Husk (RH) combustion conditions has been carried out the Combustion Laboratory of the International Islamic University Malaysia using Thermogravimetric Analyzer (TGA). The main objective of this paper is to describe the first phase of a project to use RH as a fuel for the fluidized bed combustor at universiti Kebangsaan Malaysia. Systematic investigation of the effect of process conditions on the combustion processes was carried out. This paper presents the experimental setup used in the study and the effect of combustion heating rate and oxygen composition on RH combustion processes. The effect of process conditions, such as combustion heating rate and combustion atmosphere, on rice husks combustion was quantified. The results showed that the combustion profile can be divided into three stages: the evaporation of moisture content, rapid combustion, and slower combustion with ignition.